A story of a hammer and a nail - Harun, Nur Syikri; Ismail, Fathiyah (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
A hammer; Who doesn't know what a hammer is? A nail; Who couldn't picture it in mind? They're tools that build many things A symbol for constructions is true for colonialism in disguise